2017
DOI: 10.1093/jac/dkx232
|View full text |Cite
|
Sign up to set email alerts
|

RNA and DNA Sanger sequencing versus next-generation sequencing for HIV-1 drug resistance testing in treatment-naive patients

Abstract: DSS does not clearly improve the detection of RAMs in ART-naive patients, as compared with RSS. NGS allows detection of additional minority RAMs; however, their clinical relevance requires further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 45 publications
1
21
0
Order By: Relevance
“…The resulting sam files were converted to bam files, sorted and indexed using samtools, and the sorted bam files were converted to fastq files using the bamtools software [24,25]. The resulting fastq files were analyzed with Hydra Web (Government of Canada, Ottawa, Canada) with 20% and 5% sensitivity threshold for reporting low-frequency variants [26,27,28] We used the default target coverage (10,000 reads) and filtering settings (length cutoff: 100; score cutoff: 30) in HyDRA [29]. …”
Section: Methodsmentioning
confidence: 99%
“…The resulting sam files were converted to bam files, sorted and indexed using samtools, and the sorted bam files were converted to fastq files using the bamtools software [24,25]. The resulting fastq files were analyzed with Hydra Web (Government of Canada, Ottawa, Canada) with 20% and 5% sensitivity threshold for reporting low-frequency variants [26,27,28] We used the default target coverage (10,000 reads) and filtering settings (length cutoff: 100; score cutoff: 30) in HyDRA [29]. …”
Section: Methodsmentioning
confidence: 99%
“…The average number of haplotypes per participant was the same for PR/RT and int (2 haplotypes) and slightly higher for env (4). Four of the six participants that had a higher number of haplotypes reconstructed (7)(8)(9)(10)(11)(12) haplotypes in one or more gene regions) also had a higher average haplotype diversity estimate of 0.634 (range: 0.392-0.777), while the other two had a very low average haplotype diversity estimate (0.032, range: 0.027-0.038). Participants with HRH and MSM risk factors were found to have an average of 3 reconstructed haplotypes, with haplotype diversities of 0.338 and 0.335, respectively.…”
mentioning
confidence: 97%
“…The starting material, i.e., plasma viral RNA versus proviral DNA obtained from peripheral blood mononuclear cells (PBMC) or the buffy coat fraction, can strongly influence the detection of DRMs and HIVDR test results [ 16 ]. Population sequencing on proviral DNA can introduce bias due to the inclusion of defective virus sequences, leading to an increased proportion of hypermutation and stop codons [ 17 , 18 ], especially in samples where the contribution of proviral DNA outweighs that of plasma virus RNA.…”
Section: Laboratory Considerationsmentioning
confidence: 99%
“…However, the main drawback of this technology is its inability to reliably detect low-abundance DRMs below the 20% threshold [ 1 , 39 , 40 , 41 ]. Several studies have shown that NGS-based HIVDR testing is highly concordant to Sanger sequencing at a 20% detection threshold [ 5 , 15 , 16 , 42 , 43 ]. Thus, leveraging on the potentially improved efficiency, increased scalability, decreased cost, and higher sensitivity, many laboratories are transitioning to NGS for HIVDR testing.…”
Section: Use Of Ngs For Clinical Hivdr Testingmentioning
confidence: 99%